Development And Characterization Of An Interspecific Gossypium Hirsutum X Gossypium Armourianum Hybrid (Applied Biological Research, 2016)
Interspecific hybrid between Gossypium hirsutum (AADD) cv. F 1861  and G. armourianum (DD) Acc. PAU 1 was generated and characterized  along with parents at morphological and molecular levels. Female  parent (F 1861) had erect growth habit, cream petals, palmate leaves,  green stem, cream anthers, hairy stem and leaves; whereas male parent  (PAU 1) had spreading growth habit, yellow petals, cordate leaves,  reddish green stem, yellow anthers and glabrous plant body. The growth  habit, petal colour, leaf shape and size of interspecific F1 hybrid were  intermediate. Plant stem colour and hairiness, leaf pubescence and  anther colour of G. armourianum Acc. PAU 1 were observed to be  dominant as hybrid fully resembled Acc. PAU 1 for these characters.  Petal spot was absent in F 1861 and present in PAU 1as well as hybrid.  Variable expression of petal spot, anther colour and filament colour was  observed in F1. The interspecific F1 hybrid was male-sterile. Significant  differences were observed between the pollen size of parents as well as  parents and their hybrid. Of the 33 SSR markers polymorphic between  the parents, 8 markers unambiguously confirmed the hybrid status of  interspecific hybrid. This hybrid may serve as a useful genetic resource
Keywords: American cotton; cotton leaf curl disease resistance; epigenetics; hybridization; SSR markers; wild Gossypium